INOVASI PEMBELAJARAN BERDIFERENSIASI DALAM MEWUJUDKAN KREATIFITAS PESERTA DIDIK - Yunita Azmil Arofaturrohman; Sabar Narimo; Ahmad Muhibbin; Sigit Haryanto (Postgraduate, University of Mataram, 2023)
This research explores the application of differentiated learning innovation as an effort to realize student creativity. This research uses a qualitative method with a case study approach. Case study research is an in-depth research method that explores detailed information about a particular case, entity, group, or individual. Case studies can help identify solutions to existing problems and develop recommendations for improvement. The research was conducted on fifth grade students of SD Muhammadiyah PK Rabbani Karanganom. The data taken is based on observations, documentation and interviews conducted at the school. The results of this research are one learning innovation by implementing differentiated learning using children's song media. Differentiated learning innovation for students through selecting a song related to the material. The song chosen was Islamic Ethics. Differentiated learning using songs can shape students' creativity. Students are free to create projects or tasks so that the learning process becomes fun. A differentiated learning approach not only enriches students' learning experiences, but also forms a generation of students who are creative, innovative and ready to face future demands.